Specific initial training standards are needed to dive for science in Europe, Occupational vs. Citizen Science Diving - Féral, Jean-Pierre; Norro, Alain (Frontiers in Marine Science, 2023)
Today, collaboration between scientific research and civil society is growing significantly. The general public’s curiosity drives it to engage with the scientific process and culture and in the search for solutions to complex issues (economic, social, health, environmental, cultural, educational, or ethical). Clarification is needed to differentiate between occupational scientific activity and citizen-based science. They do not require the same scientific and technical skills despite using similar equipment and their legal and administrative frameworks being totally different. The confusion created by the indiscriminate use of the same term “scientific diving” to refer to different training courses and activities compromises the quality of existing occupational standards and, ultimately, has a negative impact on the safety of the activity at work. A clear definition of Citizen Scientific Diving and Occupational Scientific Diving makes it possible to differentiate between the objectives and target groups of these two activities and their legal framework. There is a need to establish an accepted and shared standard in the occupational field and to ensure the mobility of scientists. A long process undertaken by a motivated scientific community (late 1980s-2000s) led to the establishment of European initial training standards for Occupational Scientific Diving through the ESDP-European Scientific Diving Panel (firstly under the aegis of the European Marine Board, now of the MARS-European marine stations network). The quality and general acceptance of these standards by a large part of the European scientific community have already adopted them in the occupational health and safety legislation of seven European countries (Belgium, Finland, France, Germany, Norway, Sweden, and the UK in 2023). Adopting them in other countries’ health and safety legislation is still desirable. This will increase their recognition, acceptance and use for the benefit of scientific work. Building bridges between academic science and non-academic citizen science is possible and this is done by developing coherent projects that produce results that benefit both science and society. While distinguishing between the two, as an added value, this approach could better guide the recreational diving training sector in developing a new market.